Variation in gene expression along an elevation gradient of Rhododendron sanguineum var. haemaleum assessed in a comparative transcriptomic analysis - Ye, Lin-Jiang; Möller, Michael; Luo, Ya-Huang; Zou, Jia-Yun; Zheng, Wei; Liu, Jie; Li, De-Zhu; Gao, Lian-Ming (Frontiers in Plant Science, 2023)
Selection along environmental gradients may play a vital role in driving adaptive evolution. Nevertheless, genomic variation and genetic adaptation along environmental clines remains largely unknown in plants in alpine ecosystems. To close this knowledge gap, we assayed transcriptomic profiles of late flower bud and early leaf bud of Rhododendron sanguineum var. haemaleum from four different elevational belts between 3,000 m and 3,800 m in the Gaoligong Mountains. By comparing differences in gene expression of these samples, a gene co-expression network (WGCNA) was constructed to identify candidate genes related to elevation. We found that the overall gene expression patterns are organ-specific for the flower and leaf. Differentially expressed unigenes were identified in these organs. In flowers, these were mainly related to terpenoid metabolism (RsHMGR, RsTPS), while in leaves mainly related to anthocyanin biosynthesis (RsCHS, RsF3'5'H). Terpenoids are the main components of flower scent (fragrance) likely attracting insects for pollination. In response to fewer pollinators at higher elevation zone, it seems relatively less scent is produced in flower organs to reduce energy consumption. Secondary metabolites in leaves such as anthocyanins determine the plants' alternative adaptive strategy to extreme environments, such as selective pressures of insect herbivory from environmental changes and substrate competition in biosynthesis pathways at high elevations. Our findings indicated that the gene expression profiles generated from flower and leaf organs showed parallel expression shifts but with different functionality, suggesting the existence of flexibility in response strategies of plants exposed to heterogeneous environments across elevational gradients. The genes identified here are likely to be involved in the adaptation of the plants to these varying mountainous environments. This study thus contributes to our understanding of the molecular mechanisms of adaptation in response to environmental change.